ASCEND-Eye: effects of omega-3 fatty acids on diabetic retinopathy - Sammons, E; Buck, G; Bowman, L; Armitage, J; Parish, S; Hammami, I; Stevens, W (Elsevier, 2023)
Purpose: Preclinical studies support a protective role for omega-3 fatty acids (FAs) on diabetic retinopathy (DR), but these observations have not been confirmed in randomized trials. We present randomized evidence for the effects of omega-3 FAs on DR outcomes.